LinuxDirector: A connection director for scalable internet services - Zhang, Wensong; Jin, Shiyao; Wu, Quanyuan (Journal of computer science and technology, 2000)
LinuxDirector is a connection director that supports load balancing among multiple Internet servers, which can be used to build scalable Internet services based on clusters of servers. LinuxDirector extends the TCP/IP stack of Linux kernel to support three IP load balancing techniques, VS/NAT, VS/TUN and VS/DR. Four scheduling algorithms have been implemented to assign connections to different servers. Scalability is achieved by transparently adding or removing a node in the cluster. High availability is provided by detecting node or daemon failures and reconfiguring the system appropriately. This paper describes the design and implementation of LinuxDirector and presents several of its features including scalability, high availability and connection affinity.